1970
DOI: 10.1007/bf01976763
|View full text |Cite
|
Sign up to set email alerts
|

The identification of three new viruses isolated from Wisteria and Pisum in The Netherlands, and the problem of variation within the potato virus Y group

Abstract: Three new legume diseases in The Netherlands are described: Wisteria vein mosaic, pea necrosis, and pea leafroll mosaic. In particle size and morphology and in host reaction the virus isolates resembled bean yellow mosaic virus (BYMV), but they were readily distinguishable in several test plants.In recent years several new legume viruses related to BYMV and bean common mosaic virus have been described. Besides, more and more viruses of the potato virus Y group are proving to be naturally infectious to legumes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
105
0
1

Year Published

1987
1987
1993
1993

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(123 citation statements)
references
References 39 publications
(52 reference statements)
10
105
0
1
Order By: Relevance
“…Maat, Institute for Phytopathological Research (IPO), Wageningen, The Netherlands; data not shown). The intranuclear inclusion bodies produced by all the virus isolates were identical and similar to those previously described for BYMV (BOS 1969, CHANG et al 1988. Therefore, all the virus isolates represented distinct strains ofa single vims species, namely BYMV.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Maat, Institute for Phytopathological Research (IPO), Wageningen, The Netherlands; data not shown). The intranuclear inclusion bodies produced by all the virus isolates were identical and similar to those previously described for BYMV (BOS 1969, CHANG et al 1988. Therefore, all the virus isolates represented distinct strains ofa single vims species, namely BYMV.…”
Section: Discussionsupporting
confidence: 76%
“…The pea strain of BYMV, formerly considered a distinct virus from the bean strain of BYMV and called pea mosaic virus (PMV), causes bright yellow mosaic symptoms, whereas the bean strain of BYMV causes green mosaic symptoms in pea leaves (Bos 1970b, Tapio 1970). Both strains of BYMV infect broad beans inducing similar symptoms and cytoplasmic and nuclear inclusions (Bos 1969, Tapio 1970, Cock-BAIN 1983. The bean and pea strains of BYMV occur naturally in Finland, and these strains may cause a yield loss of up to 62% and 30%, respectively, in peas depending upon the age at which the plants are infected (Tapio 1970 Kielpinski andBlixt 1982, Hovinen 1988, S. Hovinen pers.…”
Section: Introductionmentioning
confidence: 99%
“…GEOGRAPHICAL DISTRIBUTION HAMPTON & MINK (1975) (Bos, 1970) (M ATTHEWS et al, 1981) and India (T HAKUR et al, 1984). L INDSTEN et al (1976) (MI NK et al, 1969 ;K NE S EK & MINK, 1970) and Switzerland (P EL E T , 1980) and 55 % infected seed in Czechoslovakia (M USIL , 1970 (THAKUR et al, 1984).…”
mentioning
confidence: 99%
“…L INDSTEN et al (1976) (MI NK et al, 1969 ;K NE S EK & MINK, 1970) and Switzerland (P EL E T , 1980) and 55 % infected seed in Czechoslovakia (M USIL , 1970 (THAKUR et al, 1984). Above BAGGET, 1970 ;BOS, 1970 ;HAGEDORN, 1974 ;HAMPTON & MINK, 1975 ; § ZIMMER & ALI- KHAN, 1976 ; KRAFT & HAMPTON, 1980 ;PELET, 1980 ;HAMPTON, 1984) Japan (I N O UYE , 1967) and so also the differences in ultrastructural cytology (H AMPTON et al, 1973), initially suggested the existence of strains in PSbMV. However, discrepancies in reported particle lengths for PSbMV were partially resolved by H AMPTON et al (1974) (Bos, 1970) Recently three more pathotypes of PSbMV (namely P-1 and P-4 from pea, and L-1 from lentil) have been characterized on the basis of their infection of pea genotypes (ALCONERO et al, 1986 (1973).…”
mentioning
confidence: 99%
See 1 more Smart Citation